2019
DOI: 10.1371/journal.pone.0217543
|View full text |Cite
|
Sign up to set email alerts
|

Assessing arrays of multiple trail cameras to detect North American mammals

Abstract: Motion triggered camera traps are an increasingly popular tool for wildlife research and can be used to survey for multiple species simultaneously. As with all survey techniques, it is crucial to conduct camera trapping research following study designs that include adequate spatial and temporal replication, and sufficient probability of detecting species presence. The use and configuration of multiple camera traps within a single survey site are understudied considerations that could have a substantial impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 53 publications
(82 reference statements)
6
33
0
Order By: Relevance
“…It is assumed that observations obtained from a surveyed area, in this case the detection zone of a camera, are representative of the sampled site (MacKenzie et al 2017), and our data indicate information from a single camera is unlikely to meet this assumption when a site is defined as an area larger than the camera’s field of view. In addition, a multi‐camera approach has been shown, particularly for elusive species, to be a cost‐efficient approach (Gálvez et al 2016), and to result in significant improvements in detection probability (Stokeld et al 2016, O'Connor et al 2017, Evans et al 2019, Wong et al 2019), which should reduce bias in occupancy estimates (MacKenzie and Royle 2005, Bailey et al 2007, Guillera‐Arroita et al 2010, Neilson et al 2018) and potentially offset any reductions in total number of site samples (MacKenzie et al 2017). Recent work with multi‐camera sampling supports this, where conclusions about occupancy with single cameras were different from those based on the full multi‐camera design (Pease et al 2016) and multi‐camera sampling increases precision of occupancy estimates (Wong et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that observations obtained from a surveyed area, in this case the detection zone of a camera, are representative of the sampled site (MacKenzie et al 2017), and our data indicate information from a single camera is unlikely to meet this assumption when a site is defined as an area larger than the camera’s field of view. In addition, a multi‐camera approach has been shown, particularly for elusive species, to be a cost‐efficient approach (Gálvez et al 2016), and to result in significant improvements in detection probability (Stokeld et al 2016, O'Connor et al 2017, Evans et al 2019, Wong et al 2019), which should reduce bias in occupancy estimates (MacKenzie and Royle 2005, Bailey et al 2007, Guillera‐Arroita et al 2010, Neilson et al 2018) and potentially offset any reductions in total number of site samples (MacKenzie et al 2017). Recent work with multi‐camera sampling supports this, where conclusions about occupancy with single cameras were different from those based on the full multi‐camera design (Pease et al 2016) and multi‐camera sampling increases precision of occupancy estimates (Wong et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, little research has been conducted to assess the extent to which data collected at a single point are a consistent and repeatable measure of species occupancy or use at the landscape scale. Those few studies that have compared the effect of sampling single sites with variable numbers of camera stations have found that the use of single stations can severely limit detection probability for some species (Stokeld et al 2016, O'Connor et al 2017, Evans et al 2019, Wong et al 2019) and introduces bias in identification of key ecological factors influencing occupancy (Pease et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Camera-trap placement at trails optimizes the capture of large as well as small carnivores [24,25]. Also, the placement of two camera-traps at every site increased the detectability of these small felids [26]. Cameras were programmed to take three photographs per trigger with an interval of 5 sec.…”
Section: Field Methodsmentioning
confidence: 99%
“…Due to the difficulty in precisely defining effective area, prescribing spacing and number of devices is difficult and further research is needed to inform such recommendations. Nonetheless, because of our simulations, evidence from field large-scale surveys (Zielinski et al 2013, Barry 2018, and simulations for multispecies sampling design (Sun et al 2014, Wilton et al 2014, Evans et al 2019, we suspect an efficient survey method includes clusters of >2 devices within an area such that they overlap their effective sampling areas but enlarge the likelihood of detecting an animal. For example, long-term fisher monitoring in California conducts sampling within grid cells using arrays of 3-6 track plates or trail cameras spaced 500-800 m apart.…”
Section: Effective Areamentioning
confidence: 94%